Aplasia Cutis Congenita: A Simple and Safe Management - Yasir S. Jamal; Moaath Saggaf; Sabah S. Moshref; Mazen O. Kurdi; Bayan Ghabashi (Journal of King Abdulaziz University: Medical Sciences, 2023)
Aplasia cutis congenita is a rare disorder characterized by absence of the skin and skin appendages. The incidence ranges between 1:10,000 and 2.8:10,000. The management in the literature varies considerably between conservative management and surgery. A retrospective review of all the cases of aplasia cutis congenita was conducted from King Abdulaziz University Hospital, Jeddah, Saudi Arabia. The study period was from January 2004 to December 2014. Data were collected using chart review and the pictures from plastic and pediatric surgery teams. Data were analyzed using simple descriptive statistics. A total of eight cases were recruited to the study. Average follow up was two years. Six lesions were located on the scalp and two were located on the lower limbs. Seven cases were managed conservatively and one case required full thickness skin grafting for a bleeding superior sagittal sinus. Only one death was documented, and was related to a syndrome. The management of aplasia cutis congenita is related to the defect size and depth. When surgery is indicated, skin grafting is a simple, safe and highly recommended choice of surgical management for the coverage of the skin defect and to control bleeding from underlying superior sagittal sinus in deep lesions.